Revitalize the Sungai Baru river as a recreational corridor with sustainable tourism planning at Kuala Sungai Baru, Malacca/ Norlyana Ya'akop - Ya'akop, Norlyana (2017)
River plays an important role in providing an excellent habitat and food for many of the earth's organisms. In contribution of tourism, river becomes the focus area and it should encourage the tourist by providing spectacular settings, recreation facilities, a means of transport, a sense of heritage and adventure and links with the environment and natural world. The purpose of the river is to set a vision for a recreation corridor along the Sungai Baru river, Kuala Sungai Baru, Malacca. It examines the existing condition along the Sungai Baru river as well as feedback from the general public on the desire for more local recreational opportunities along the Sungai Baru river. It needs more to develop an integrated system of parks, recreation, open space and connectivity within the river corridor. The methodology of this study involves the accomplishment stages of secondary data from the government department and existing data from earlier researchers which already published. The primary data has been collected through observation and data recorded method. All collected data are synthesized to identify the potential area to be developed and preserved. Hopefully, this project can be used as design strategies and guidelines for stakeholders in revitalizing the Sungai Baru river as a recreational corridor.